1996
DOI: 10.1007/bf02602587
|View full text |Cite
|
Sign up to set email alerts
|

Chicken B-cell marker chB6 (Bu-1) is a highly glycosylated protein of unique structure

Abstract: The chB6 molecule is expressed on chicken B cells throughout most of their development, as well as on some non-lymphoid cells. It has long been used as an allotypic marker in important studies of B-cell development, though its function is unknown. We isolated a chB6 cDNA by expression cloning and sequenced two further alleles following polymerase chain reaction amplification. The results show that chB6 is a typical type I transmembrane protein, highly glycosylated in the extracellular region and carrying a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 27 publications
2
52
0
Order By: Relevance
“…The monoclonal antibody to Bu-1 used in this study recognizes immature cells but not the antibody-producing plasma cells that are mature cells (Veromaa et al, 1988b;Mansikka et al, 1989;Tregaskes et al, 1996) (Yoshimura et al, 1997a Wira, 1979). Severe atrophy of the bursa and an increase in plasma cell population in the oviduct have been observed in DEStreated chickens (Khan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The monoclonal antibody to Bu-1 used in this study recognizes immature cells but not the antibody-producing plasma cells that are mature cells (Veromaa et al, 1988b;Mansikka et al, 1989;Tregaskes et al, 1996) (Yoshimura et al, 1997a Wira, 1979). Severe atrophy of the bursa and an increase in plasma cell population in the oviduct have been observed in DEStreated chickens (Khan et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…2A). Phycoerythrinlabeled anti-BU-1 (Cambridge Bioscience, Cambridge, United Kingdom) recognizes chicken B cells (23,25) and was used for fluorescence-activated cell sorting analysis. As expected, both surgical bursectomy and cylophosphamide treatment effectively removed B cells from the spleen (0.34% and 0.63% Bu1 ϩ cells, respectively, compared with 19.80% with intact animals) (Fig.…”
mentioning
confidence: 99%
“…This observed 5hmC reduction in bursal tissue sections was validated by a dot blot assay ( Figure 1B) which shows a progressive reduction in genomic 5hmC from ED16 to seven days posthatch (D7). To confirm that the proliferating follicles did contain B-cells we co-stained ED18 bursal sections with Bu-1, an avian B-cell marker [26], and either an antibody directed to 5mC or 5hmC. We found that Bu-1 only stained cells within each follicle and the majority of these B-cells were also highly enriched for 5mC (Figure 2A).…”
Section: Resultsmentioning
confidence: 85%